Characterization of ovarian follicular and cystic fluids in cows - Nora Mimoune; Rachid Kaidi; Abdelmoumène Guedioura; Hocine Mohamed Benaissa; Yassine Mohamed Azzouz (Veterinaria, 2018)
The study was aimed at evaluating the hormonal, histological and metabolic changes associated with ovarian cyst (OC) formation in cows. For this purpose, , the ﬂuid was aspirated from 195 ovarian cysts and 120 ovarian large follicles collected at a local abattoir in order to assess their hormonal concentrations and metabolic changes. Pieces of the cyst wall tissue were subjected to histologic evaluation. Data showed that the cysts’ fluid was characterized by the lower concentrations of glucose, cholesterol, total protein and higher urea levels than those of the large follicles (P<0.001). However, insulin, creatinine, total bilirubin, GGT, AST, ALT and alkaline phosphatase concentrations were not signiﬁcantly different between the both fluids. Large follicles and follicular cysts’ fluids showed higher concentrations of estradiol than the luteal cysts. Conversely, higher levels of progesterone were observed in the luteal cysts’ fluid. Follicular cysts and large follicles mostly had estradiol-to-progesterone (E/P) ratio > 1, whereas the luteal cysts all had E/P ratio < 1. It can be speculated that the abnormal levels of some biochemical and hormonal parameters may lead to follicle dysfunction resulting in cyst formation. Keywords: ovary, cyst, biochemistry, hormone, cow